2011
DOI: 10.4028/www.scientific.net/amr.331.93
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Modified Cotton Textiles

Abstract: The graphene oxides are abundant in hydroxyl and carboxyl groups that are close to the reactive dyes. These structural features gave a possibility to modify textiles to enhance the conductivity by using the dyeing and finishing method. Herein, graphene modified cotton textiles are fabricated by soaking cotton cloth in graphene oxide colloid. After reduction, the modified textiles exhibit an improved conductivity. The present work contributed a facile strategy for graphene modified textiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Fugetsu et al [22] reported resistance values ranging from 10 2 to 10 9 Ω/cm depending on the RGO content for the deposition of RGO on polyarylate. Gu et al [23] obtained resistances of 2.01·10 7 Ω for one coating process of RGO on cotton fabrics. The necessity of more coating processes to achieve low resistances in the case of employing graphene sheets [21] could be explained by the low adhesion of graphene on polyester fabrics due to the low presence of polar groups on graphene sheets.…”
Section: Fabrics (Pes Pes-go Pes-1g Pes-2g Pes-3g Pes-4gmentioning
confidence: 99%
See 2 more Smart Citations
“…Fugetsu et al [22] reported resistance values ranging from 10 2 to 10 9 Ω/cm depending on the RGO content for the deposition of RGO on polyarylate. Gu et al [23] obtained resistances of 2.01·10 7 Ω for one coating process of RGO on cotton fabrics. The necessity of more coating processes to achieve low resistances in the case of employing graphene sheets [21] could be explained by the low adhesion of graphene on polyester fabrics due to the low presence of polar groups on graphene sheets.…”
Section: Fabrics (Pes Pes-go Pes-1g Pes-2g Pes-3g Pes-4gmentioning
confidence: 99%
“…Regarding conducting fabrics coated with graphene and its derivatives very little has been reported [21][22][23]. Yu et al deposited graphene directly on the fabrics and later electrodeposited MnO 2 to produce supercapacitors [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process is similar to a dying process where an adsorption process occurs [16]. Once the fabric is coated with GO, it is then reduced to RGO using reducing agents such as sodium hydrosulfite [16], hydrazine [17], etc. GO coated fabrics have also generated interest due to the photo-catalytic activity of GO and also to its antibacterial activity [18].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene-coated fabrics have usually been obtained by placing the fabrics in contact with solutions containing GO [16,17]. GO sheets are adsorbed on the surface of the fabrics due to the attraction forces between the functional groups of the fabrics and the oxidized groups of the GO sheets.…”
Section: Introductionmentioning
confidence: 99%